Life Satisfaction Among Healthcare Volunteers in Malaysia: Role of Personality Factors, Volunteering Motives, and Spiritual Capital - Veerasamy, Chanthiran; Sambasivan, Murali; Kumar, Naresh (Springer US, 2014)
This article analyzes the role of three antecedents of life satisfaction (LS) among healthcare volunteers in Malaysia. The antecedents are: personality traits, motives to volunteer, and spiritual capital. This study has empirically tested the impact of individual dimensions of personality traits, motives, and spiritual capital along with their inter-relationships in explaining the LS. The volunteers of St. John Ambulance participated in this study. The model has been tested using structural equation modeling and it has been found that the three constructs have an explanatory power of 53 %. The main results are: (1) neuroticism, value motives, protective motives, personal well-being, and spirituality have a direct impact on LS and (2) enhancement motives, social motives, and religiosity have an indirect impact on LS. These results can provide insights to researchers and managers regarding profiling the right volunteers, providing the necessary infrastructure, and providing proper training to the volunteers.